What makes coaches tick? The impact of coaches' intrinsic and extrinsic motives on their own satisfaction and that of their athletes - Jowett, S. (Scandinavian Journal of Medicine & Science in Sports, 2008)
This study aims to investigate the influence of two types of motivational forces on coach and athlete satisfaction. The focus is on intrinsic and extrinsic motives that initiate coach-related behavior. A questionnaire that measures both types of motivation and three facets of satisfaction (i.e., satisfaction with performance, with instruction, and with the coach-athlete relationship) was completed by 138 coaches. One athlete from each of the coaches who participated in the study was also asked to complete a questionnaire that measures their satisfaction with performance, instruction, and the coach-athlete relationship. Results from a series of regression analyses indicated that while intrinsic motivation was moderately and positively related to all facets of coach satisfaction, extrinsic motivation was only related to coach satisfaction with the coach-athlete relationship. Athletes' satisfaction with the coach-athlete relationship was only associated with the coach's intrinsic motivation. Interaction effects among the two types of motivation were significant suggesting that extrinsic motivation can potentially undermine intrinsic motivation when intrinsic motivation is low. The findings are discussed based on assumptions put forward by self-determination theory.